Terrorism and Immigration Policy Preferences - Marc Helbling; Daniel Meierrieks; Sergi Pardos-Prado (Defence and Peace Economics, 2022)
What is the causal impact of terrorism on immigration policy preferences? Under what circumstances and due to which psychological micro-mechanisms does this impact materialize? To answer these questions, we provide evidence from pre-registered and well-powered experiments for Germany and the United Kingdom. We find that anti-immigration responses to terrorism follow an emotional proximity rationale: terrorism leads to more restrictive migration policy preferences only among individuals with high levels of perceived insecurity, especially when terrorism occurs in their own country. Policy preferences are not affected by terrorism abroad or by information cues on the objectively low probability of being victimized.
Keywords: 330; terrorism; migration; migration policy; survey experiment; fearfulness